2020
DOI: 10.1101/2020.11.01.364257
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RNA-seq analysis of laser micro-dissected Arabidopsis thaliana leaf epidermis, mesophyll and vasculature defines tissue-specific transcriptional responses to multiple stress treatments

Abstract: Acclimation of plants to adverse environmental conditions requires the coordination of gene expression and signalling pathways between tissues and cell types. As the energy and carbon capturing organs, leaves are significantly affected by abiotic and biotic stresses. However, tissue- or cell type-specific analyses of stress responses have largely focussed on the Arabidopsis root. Here, we comparatively explore the transcriptomes of three leaf tissues (epidermis, mesophyll, vasculature) after induction of diver… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 129 publications
(207 reference statements)
1
3
0
Order By: Relevance
“…WAX2, which has a metabolic function associated with both cuticle membrane and wax synthesis (Chen et al, 2003), was highly expressed in upper epidermal cells, whereas DIN6, which is involved in nitrogen metabolism repressed by light (Lam et al, 1998), was highly expressed in the lower epidermis (Figure 3D). Since guard cells were excluded from the epidermal cell in our dataset, this result indicates that epidermal pavement cells have photosynthetic capacity, consistent with the finding that pavement cells of Arabidopsis have chloroplasts (Barton et al, 2016;Berkowitz et al, 2021). For mesophyll cell subtypes, we observed that photosynthesis-related GO terms were significantly enriched in the palisade mesophyll, while stress-related GO terms were enriched in spongy mesophyll cells, which is suggestive of functional distinction as well (Figure S4D).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…WAX2, which has a metabolic function associated with both cuticle membrane and wax synthesis (Chen et al, 2003), was highly expressed in upper epidermal cells, whereas DIN6, which is involved in nitrogen metabolism repressed by light (Lam et al, 1998), was highly expressed in the lower epidermis (Figure 3D). Since guard cells were excluded from the epidermal cell in our dataset, this result indicates that epidermal pavement cells have photosynthetic capacity, consistent with the finding that pavement cells of Arabidopsis have chloroplasts (Barton et al, 2016;Berkowitz et al, 2021). For mesophyll cell subtypes, we observed that photosynthesis-related GO terms were significantly enriched in the palisade mesophyll, while stress-related GO terms were enriched in spongy mesophyll cells, which is suggestive of functional distinction as well (Figure S4D).…”
Section: Resultssupporting
confidence: 89%
“…Based on the DEG analysis results, we captured cell-type-specific clusters of genes (Figures 3D and S4C; Table S3). The following Gene Ontology (GO) term analysis of DEGs for upper versus lower epidermal cells revealed that biological processes associated with photosynthesis (Berkowitz et al, 2021), cuticle development, and fatty acid biosynthesis were significantly enriched in upper epidermal cells, while biological terms related to immune response, response to absence of light, and regulation of cell death were significantly enriched in lower epidermal cells (Figure 3E). WAX2, which has a metabolic function associated with both cuticle membrane and wax synthesis (Chen et al, 2003), was highly expressed in upper epidermal cells, whereas DIN6, which is involved in nitrogen metabolism repressed by light (Lam et al, 1998), was highly expressed in the lower epidermis (Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations